Impact of a surgical site infection reduction strategy after colorectal resection. (September 2016) - Connolly, T. M.; Foppa, C.; Kazi, E.; Denoya, P. I.; Bergamaschi, R.
Abstract: Aim: This study was performed to determine the impact of a surgical site infection (SSI) reduction strategy on SSI rates following colorectal resection. Method: American College of Surgeons National Surgical Quality Improvement Program (NSQIP) data from 2006–14 were utilized and supplemented by institutional review board‐approved chart review. The primary end‐point was superficial and deep incisional SSI. The inclusion criterion was colorectal resection. The SSI reduction strategy consisted of preoperative (blood glucose, bowel preparation, shower, hair removal), intra‐operative (prophylactic antibiotics, antimicrobial incisional drape, wound protector, wound closure technique) and postoperative (wound dressing technique) components. The SSI reduction strategy was prospectively implemented and compared with historical controls (pre‐SSI strategy arm). Statistical analysis included Pearson's chi‐square test, and Student's t ‐test performed withspss software. Results: Of 1018 patients, 379 were in the pre‐SSI strategy arm, 311 in the SSI strategy arm and 328 were included to test durability. The study arms were comparable for all measured parameters. Preoperative wound class, operation time, resection type and stoma creation did not differ significantly. The SSI strategy arm demonstrated a significant decrease in overall SSI rates (32.19% vs 18.97%) and superficial SSI rates (23.48% vs 8.04%). Deep SSI and organ space rates did not differ. A review of patients testing durability demonstrated continued improvement in overall SSI rates (8.23%). Conclusion: The implementation of an SSI reduction strategy resulted in a 41% decrease in SSI rates following colorectal resection over its initial 3 years, and its durability as demonstrated by continuing improvement was seen over an additional 2 years.